Komunikasi Persuasif dan Sikap Pada Perundungan dalam Serial Film 13 Reasons Why - Roma Kristian Eleazar; Deddy Irwandy (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Nowadays, the condition of bullying cases committed by teenagers in Indonesia is still high, and it remains an unresolved issue, as well as the enthusiasm of Netflix viewers in Indonesia steadily increases, where the